PENINGKATAN KOMPETENSI GURU TAMAN KANAK-KANAK KOTA SEMARANG DALAM MEMBUAT ALAT BERMAIN SAINS DARI LIMBAH - Yulianti, Dwi; H., S.S. Dewanti (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
This community service activity purposes to growth teacher competence tool of play science (ABS) for kindergaten education. The method are training and workshop including lectures, demonstration method and peer teaching.The ABS was made are colourful plaited mat, gravitation, measuring out, magnetic and sound etc. After that there is an increasing the quantity of tool in each school. Also an increasing teacher competence to made science tool of play (ABS). The peer teaching show that the resul learning cognitif, afective and phycomotoric increse sicnificantly.